2022
DOI: 10.1002/aic.17810
|View full text |Cite
|
Sign up to set email alerts
|

A high‐throughput chaotic advection microreactor for preparation of uniform and aggregated barium sulfate nanoparticles

Abstract: A high-throughput (105.5 g/h) passive four-stage asymmetric oscillating feedback microreactor using chaotic mixing mechanism was developed to prepare aggregated Barium sulfate (BaSO 4 ) particles of high primary nanoparticle size uniformity. Threedimensional unsteady simulations showed that chaotic mixing could be induced by three unique secondary flows (i.e., vortex, recirculation, and oscillation), and the fluid oscillation mechanism was examined in detail. Simulations and Villermaux-Dushman experiments indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…In addition, the three unique secondary flows (i.e., vortex, feedback, oscillation) can effectively induce chaotic advection, causing the fluids to stretch, fold, and compress, significantly shortening the molecule diffusion distance and improving fluid mixing and mass/heat transfer. Hence, homogeneous concentration and temperature fields could be achieved in OFMs for preparing high-quality nanoparticles with a narrow PSD at high throughput. Lately, we demonstrated that OFMs could be applied for high-throughput production of inorganic nanoparticles, where small samples with narrow PSD could be effectively prepared. However, OFMs have never been used to prepare ZIF-67 or other metal–organic framework materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the three unique secondary flows (i.e., vortex, feedback, oscillation) can effectively induce chaotic advection, causing the fluids to stretch, fold, and compress, significantly shortening the molecule diffusion distance and improving fluid mixing and mass/heat transfer. Hence, homogeneous concentration and temperature fields could be achieved in OFMs for preparing high-quality nanoparticles with a narrow PSD at high throughput. Lately, we demonstrated that OFMs could be applied for high-throughput production of inorganic nanoparticles, where small samples with narrow PSD could be effectively prepared. However, OFMs have never been used to prepare ZIF-67 or other metal–organic framework materials.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the ordered microreactors, it was disclosed that oscillating feedback microreactors (OFMs) based on chaotic advection can operate at high Reynolds numbers (i.e., high throughput, at Reynolds numbers of 10 2 –10 3 ), which is much larger than those of the ordered lamination flow and segmented flow microreactors (i.e., at Reynolds numbers of 10 –1 –10 2 ) . In addition, the three unique secondary flows (i.e., vortex, feedback, oscillation) can effectively induce chaotic advection, causing the fluids to stretch, fold, and compress, significantly shortening the molecule diffusion distance and improving fluid mixing and mass/heat transfer. Hence, homogeneous concentration and temperature fields could be achieved in OFMs for preparing high-quality nanoparticles with a narrow PSD at high throughput. Lately, we demonstrated that OFMs could be applied for high-throughput production of inorganic nanoparticles, where small samples with narrow PSD could be effectively prepared.…”
Section: Introductionmentioning
confidence: 99%